Analisis ANALISIS PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA MENGGUNAKAN MODEL INKUIRI TERBIMBING BERDASARKAN N-GAIN - Tania Oktatinari; An Nuril Maulida Fauziah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the improvement of students’ critical thinking skills through the implementation of the guided inquiry learning model. This research used a quantitative approach with a pre-experimental design in the form of one group pretest-posttest. The subjects were 30 students of class VIII-B at SMP Negeri 5 Surabaya in the 2025/2026 academic year. The instruments used included critical thinking tests, observation sheets of learning implementation, and student response questionnaires. Data were analyzed using N-Gain, normality test, paired sample t-test, and Wilcoxon test. The results showed that the average N-Gain score was 0.82 (high category). A total of 77% of students were in the high category and 23% in the medium category. Learning implementation reached 100% (very good), and student responses were in the very good category. Thus, the guided inquiry learning model is effective in improving students' critical thinking skills.